Ibn Taymiyya and the attributes of God - Suleiman, Farid 1983- (Brill, 2024)
"In Ibn Taymiyya and the Attributes of God (orig. published in German, 2019), Farid Suleiman pieces together, on the basis of statements scattered unsystematically over numerous individual treatises, an overall picture of the methodological foundations of Ibn Taymiyya's doctrine of the divine attributes. He then examines how Ibn Taymiyya applies these foundational principles as exemplified in his treatment of selected divine attributes. Throughout the book, Suleiman relates Ibn Taymiyya's positions to the larger context of Islamic intellectual history. The book was awarded the Dissertation Prize 2019 by the Academy for Islam in Research and Society (AIWG) and the Classical Islamic Book Prize by Gorgias Press (2020)"--
Keywords: Ibn Taymīyah, Aḥmad ibn ʻAbd al-Ḥalīm / 1263-1328; God (Islam) / Attributes; Islam / History of doctrines; Dieu (Islam) / Attributs; Islam / Histoire des doctrines; Hochschulschrift